A novel oligonucleotide pair for genotyping members of the pseudomonas genus by single-round PCR amplification of the gyrb gene - Agaras, Betina Cecilia (2018)
Pseudomonas is a phylogenetically diverse bacterial genus which is broadly distributed in different ecological niches, and whose taxonomy is continuously under revision. For that purpose, gyrB is one of the housekeeping genes routinely used for multilocus sequence analysis (MLSA). As we noticed that there was not a single primer pair available in the literature suitable for direct sequencing of this gene, we decided to design a unique oligonucleotide pair and to set up a polymerase chain reaction (PCR) protocol to obtain a single amplicon for the entire Pseudomonas genus. Based on the available gyrB sequence from 148 Pseudomonas species, we identified highly conserved regions to design oligonucleotides without fully degenerate positions. We then set up cycling conditions for achieving high specificity and yield of the PCR protocol. Then, we showed that the amplicons produced with this procedure were appropriate for direct sequencing with both primers, obtaining more than 95% of amplicons coverage. Finally, we demonstrated that a PCR-RFLP (restriction fragment length polymorphism) approach served to differentiate among Pseudomonas species, and even between members of the same species.